PERAN PEMANFAATAN TEKNOLOGI INFORMASI DALAM PENINGKATAN KINERJA PEGAWAI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL DI KABUPATEN BULELENG (STUDI EKONOMI PUBLIK) - Dharma Hartawan, I Gusti Made; Juniartini, Putu Ayu (Universitas Panji Sakti, 2024)
This research aims to determine the role of the use of information technology in improving the performance of Population and Civil Registration Service employees in Buleleng Regency. The results of this research show that the improvement in the performance of Buleleng Regency Disdukcapil employees as seen from service to the community is good because they have used the KEMENDAGRI Digital Population Identity Application and employees have been able to complete performance targets in accordance with the job descriptions of each employee as outlined in the system. The role of the use of technology and information in improving the performance of Buleleng Regency Dukcapil Disdukcapil employees, namely available work equipment facilities, clear SOPs, good working conditions and atmosphere and support and appreciation from superiors as well as employee competence, employee willingness and seriousness in carrying out their duties. The strategy used in an effort to improve employee performance at the Buleleng Regency Dukcapil Office is by planning an organizational program, namely the process of planning, organizing, leading and controlling the efforts of members of the organization as well as utilizing all organizational resources in order to achieve organizational goals that have been determined by the leadership.